2015
DOI: 10.1016/j.jcv.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of respiratory viruses and etiology of human rhinovirus infection in children

Abstract: Seasonal distribution was seen for each virus. There were no significant differences in clinical symptoms in the children studied. Because the infection of rhinoviruses is the common occurrence in children, it is hypothesized that the factors related to disease severity are mainly the underlying conditions of the children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 25 publications
3
39
1
1
Order By: Relevance
“…The high number of RSV positive children, their young age, high admission rate and high DSS was expected since RSV is well known to have a great disease burden in young children [20]. RV usually is the most frequently found virus in young children and Enteroviridae peak in late summer and autumn [21]. However, in our study, RV was not frequently found as a single pathogen, possibly due to the sampling period in the winter.…”
Section: Single Infectionsmentioning
confidence: 52%
See 1 more Smart Citation
“…The high number of RSV positive children, their young age, high admission rate and high DSS was expected since RSV is well known to have a great disease burden in young children [20]. RV usually is the most frequently found virus in young children and Enteroviridae peak in late summer and autumn [21]. However, in our study, RV was not frequently found as a single pathogen, possibly due to the sampling period in the winter.…”
Section: Single Infectionsmentioning
confidence: 52%
“…The mean age of children positive for FLU was relatively high and most children were infected during the second winter season in their life. A possible explanation for this phenomenon is that the influenza-season lasts only a few weeks during a winter season [21]. As adults are also frequently infected, young children may be protected by circulating maternal antibodies against FLU during the first months of their life [27].…”
Section: Single Infectionsmentioning
confidence: 99%
“…In this study, was observed no seasonality for rhinovirus infections. Morikawa et al primarily detected HRV type C in winter, whereas type A rhinovirus was detected throughout the year. This study did not assess all rhinovirus types, which may produce its occurrence throughout the year in the population studied.…”
Section: Discussionmentioning
confidence: 99%
“…virus, human coronavirus, and human respiratory syncytial virus (RSV) clearly show peak incidences in the winter months (leading to them sometimes being called winter viruses) (14,(27)(28)(29)(30)(31). Conversely, adenovirus, human bocavirus, human metapneumovirus (hMPV), and rhinovirus can be detected throughout the year (all-year viruses) (30)(31)(32). For some enteroviruses, detection frequency and case numbers increase in summer (summer viruses) (33,34).…”
Section: Seasonality Of Respiratory Viruses In the Human Populationmentioning
confidence: 99%